Online faculty development: What works? - Anita Samuel (Adult Education Research Conference, 2016)
This paper presents the findings of a qualitative study conducted with online faculty. Faculty talked about the training and support services they utilized and found most effective when teaching online.
Keywords: online; faculty; development